HUBUNGAN ANTARA LEVEL TRIASE DENGAN LAMA WAKTU TUNGGU PASIEN IGD RSUD PROF. DR. MARGONO SOEKARJO PURWOKERTO - Angky, Putrama; Endiyono; Mustiah Yulistiani; Sri Suparti (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2024)
Background: The Emergency Department (ED) serves as the initial handling unit for patients who are ill or injured, aiming to provide rapid and accurate care to enhance patient satisfaction and reduce waiting times. Effective triage is essential for prioritizing patient care based on urgency Purpose: To examine the correlation between triage level and patient waiting time in the Emergency Department of RSUD (Regional Public Hospital) Prof. Dr. Margono Soekarjo Purwokerto Methods: This study employs a descriptive quantitative observational design with a cross-sectional approach. Purposive sampling was used to select 94 samples, focusing on patients categorized into triage levels 1, 2, and 3. Data collection was conducted using an observation sheet. Data processing and analysis were performed using SPSS with Spearman’s rank correlation test Result: The majority of respondents were male (51.1%), with ages ranging from 18 to 87 years, averaging 49.9 years (adult category). The most prevalent medical diagnosis was palliative care with a general cancer diagnosis (16%). The majority of patients were first-time visitors (54.3%). Triage level 2 (yellow label) was the most common (50%), with an average waiting time of 357.93 minutes (approximately 5.97 hours), categorized as fast. Statistical testing revealed a p-value of 0.000 Implication: There is a significant correlation between triage level and patient waiting time in the Emergency Department of RSUD Prof. Dr. Margono Soekarjo Purwokerto